Journey into space the visual odyssey of Fernando Zobel. (Ayala Foundation, Inc., 2014)
This exhibition aims to continue the narrative on the work of the artist explored in the exhibition organized in 2009 at the Ayala Museum, Fernando Zobel in the 1950s: the Formative Years. That exhibition focused on the drawings and early figurative paintings of Zobel in the early 1950s and how this phase was the gateway towards the flight to pure abstraction. On the thirtieth death anniversary of Fernando Zobel, the new exhibition will revisit the visual odyssey of the artist--how he move on from the earlier concern with national identity and evolved from calligraphic and gestural black and white paintings, to painting air, atmosphere, and empty, white space. A survey of Zobel's works through the years is a visual progression of the mastery and control of material, technique and creativity, informed and embodied by an intellectual mind. A journey, as art critic Eric Torres described it, from the material to the spiritual.